1983
DOI: 10.1128/aac.24.5.754
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of enoxacin, a quinolone carboxylic acid, compared with those of norfloxacin, new beta-lactams, aminoglycosides, and trimethoprim

Abstract: Enoxacin is a new quinolone carboxylic acid compound. Its activity against 740 bacterial isolates was determined. It inhibited 90% Escherichia coli, Klebsiella sp., Aeromonas sp., Enterobacter spp., Serratia spp., Proteus mirabilis, and Morganella morganii at -0.8 ,ug/ml. The majority of Pseudomonas aeruginosa was inhibited by <3.1 p.g/ml. Haemophilus spp. and Neisseria spp. were inhibited by <0.1 jig/ml. Although most Staphylococcus aureus were inhibited by 3.1 ,ug/ml, some streptococcal species had minimal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 6 publications
7
61
0
Order By: Relevance
“…Macrophage colonystimulating factor (CSF-1) was obtained from Peprotech. Enoxacin was obtained from Sigma-Aldrich and dissolved in DMSO (1) or 0.1 M sodium hydroxide (32).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophage colonystimulating factor (CSF-1) was obtained from Peprotech. Enoxacin was obtained from Sigma-Aldrich and dissolved in DMSO (1) or 0.1 M sodium hydroxide (32).…”
Section: Methodsmentioning
confidence: 99%
“…One of these revertants was characterized in more detail and shown to be indistinguishable in all properties from the pretherapy isolate. It is proposed that the multiple-antibiotic-resistance (Mar) phenotype of this mutant resulted from a single pleiotropic mutation.Enoxacin is a difluorinated quinolone with strong activity for gram-negative bacteria (7,41). Enoxacin is now marketed in 11 countries, including South America, the United Kingdom, and other parts of Europe, for use in the therapy of urinary tract infections and in some countries for respiratory tract infections.…”
mentioning
confidence: 99%
“…Enoxacin is a difluorinated quinolone with strong activity for gram-negative bacteria (7,41). Enoxacin is now marketed in 11 countries, including South America, the United Kingdom, and other parts of Europe, for use in the therapy of urinary tract infections and in some countries for respiratory tract infections.…”
mentioning
confidence: 99%
“…Generally, the 7-piperazinyl enoxacin have better Gram-negative than Gram-positive antimicrobial potency (Chin & Neu, 1983, Paton & Reeves, 1988, Wood, 1989. Studies revealed that the mode of action of quinolones involves inhibition of essential type II bacterial topoisomerases such as DNA gyrase and topoisomerase IV (Sissi & Palumbo, 2003).…”
Section: Antibacterial Activitymentioning
confidence: 99%